The Relationship Between Leverage, Maturity, and Investment Decision: Evidence From Emerging Markets - Nugroho, Vina Christina; Suk, Kim Sung (Organizations and Markets in Emerging Economies, 2019)
In this paper, we examine simultaneous relationship between leverage, maturity and over(under)- investment in emerging markets. We divide leverage into short term and long term to investigate the relation between current and future simultaneous relationship between leverage and investment decision, between debt maturity and investment decision, and between leverage and debt maturity. This research used twenty emerging market data from 2006 – 2016. First of all, our results show that firms in emerging markets prefer to use short-term debt to long-term debt to minimize the underinvestment problem. Second, there is a simultaneous non-linear relation between long-term leverage and growth opportunities in emerging markets firms. Third, long-term debt has non-linear effects on investment decision in emerging markets firms. It can be concluded that firms in emerging markets have different characteristics with regard to their capabilities to manage the interaction between leverage, maturity and investment compared to developed markets.
Keywords: leverage; debt maturity; investment; emerging markets